ESTETIKA BAHASA DAN PENDIDIKAN BUDI PEKERTI DALAM ANTOLOGI GEGURITAN SIMBOK SERTA RELEVANSINYA SEBAGAI BAHAN AJAR BAHASA JAWA KELAS IX SMP - Setyawan, Budi; Sulaksono, Djoko; Wijayanti, Kenfitria Diah (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2020)
This research aims to explain (1) the aesthetic element of language that found in the anthology of Javanese poetry “Simbok”; (2) the value of character education that found in the anthology of Javanese poetry “Simbok”; (3) the relevance of Javanese poetry anthology “Simbok” as Javanese language teaching material for grade 9th Junior High School students. This is a descriptive qualitative research that uses document analysis method with a stylistic approach. The data source is a document in the form of an anthology of Javanese poetry “Simbok” and informants who are literary expert. Data collection is done by using documentation and interview techniques, then tested for the validity of the data using source triangulation and technical triangulation. The sequence of data analysis in this research includes data collection, data reduction, data presentation, and draw the conclusion. The result of this research obtained (1) the findings of language aesthetic elements in the form of the use of basa rinengga including tembung saroja, tembung garba, tembung plutan, tembung mawa aksara lira-liru, keratabasa, tembung entar, paribasan, saloka, cangkriman, dasanama, pepindan, gugontuhon, and purwakanti; (2 )the findings of character education values include religiousity, social, gender, justice, democracy, honesty, self determination, struggling ability, responsibility, and respect for nature; (3) the relevance of Javanese poetry anthology “Simbok” as teaching material for grade 9th Junior High Scool students. Based on the research result, the anthology of Javanese poetry “Simbok” is relevant to be used as Javanese language teaching material in learning to write a Javanese poetry because there are many examples of language aesthetics and character education values that are useful to help students learn to write Javanese poetry.